Hoverbike / Nabilah Naharudin, Nursyafika Sahrin … [et al.] - NAHARUDIN, NABILAH; SAHRIN, NURSYAFIKA; MOHD ASRI, NUR ALIAH ADILLA; BUNIRAN, NOR SHAFIKA; ABD AZIZ, MOHD QAEDI FAIZ (2018)
The production of modern hoverboard nowadays gave many negative drawbacks to customer in terms of safety and comfort. In order to overcome the issues, new invention of hoverboard, invented as hover bike are designed perfectly to fulfil the customer's demand. Hover bike is classified as one type of mobile personal transport similar to skateboard, but using magnetic means of levitation instead of wheels. This new product had so many additional features that will help the customer ease their routine in daily life such as solar shade with USB port and compressible seat. The new features give more comfort and more user friendly to the future customer. In conjunction with that, there are several objectives of this invention, which are to design a more stabilize hoverboard, to reduce the dependency of using electric as energy sources and the most important one is to ensure the safety of the customer. However, this hoverbike has its own limitations, which are its limit in accessibility and weight limitation. A concept survey was conducted by distributing a set of questionnaires to any possible customers such as students, staffs and netizen around Seksyen 7, Shah Alam, Selangor. There are six (6) classes of new product development (NPD) including new-to-the-world-products, new product lines, additions to the existing product lines, improvements and revisions of existing products, repositioning and cost reductions. Besides, there are several steps that need to be followed accordingly in the process of new product design. Firstly, it is needed to do some research &development that consists of idea generation, idea screening and market survey. Next, the product needs to be designed and show their specific features that differ them with another existing product. Before building the prototype (either in 2D or 3D), the concept needs to be tested first by conducting a survey to get information about customer's need as many as possible. Only then, the completed prototype could be viewed by others to test whether they are willing to buy such product or not. This last step is called as test marketing product process, which in this case the testing is conducted by distributing a set of questionnaires to the possible customers. All in all, the new product design is a successful design to be proud of after finishing it according to the steps that were highlighted in the new product development process..